Appendiceal low-grade pseudomyxoma peritonei recurrence with splenic invasion and parastomal hernia - Liu, Qi; Jiao, Jie; Yu, Guanying; Guo, Peiming; Li, Chengzhen (Frontiers in Surgery, 2024)
Recurrence of low-grade appendiceal pseudomyxoma peritonei (PMP) with splenic invasion and parastomal hernia is exceptionally rare. We present a 47-year-old female with recurrent PMP, four years post-cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC). She presented with abdominal distension, splenic invasion, and parastomal hernia. Imaging revealed extensive peritoneal and pelvic metastases, splenic lesions, and parastomal hernia. Intraoperative findings confirmed widespread pseudomyxoma, involving the spleen and diaphragm. She underwent CRS, splenectomy, tumor resection, adhesiolysis, partial colectomy, hernia repair, and diaphragmatic reconstruction, followed by intraoperative HIPEC. Despite postoperative complications, the patient recovered well with no recurrence over 20 months. This case underscores the challenges of managing recurrent PMP with splenic metastases and parastomal hernias, highlighting the importance of multidisciplinary collaboration and personalized therapeutic strategies.